The Politics of Religious Recognition: A Comparative Study of Modern Government Policies in Indonesia and Turkey - Maulana, Muhamad Silva (Dinasti Research, 2025)
This study aims to analyze the politics of religious recognition through modern government policies in Indonesia and Turkey and compare the implications of the secularism model adopted on the position of religion in the public sphere. Religious recognition is a fundamental aspect of modern governance because it is directly related to the legitimacy of the state and socio-political stability. These two Muslim-majority countries allocate large proportions of the budget for religious administration despite adhering to the principle of secularism. This study uses a qualitative approach with a comparative study method through comparative policy analysis and comparative techniques between countries. Secondary data were collected through documentation studies and systematic literature analysis of policy documents, laws and regulations, and academic literature. The results of the study show that Indonesia implements the model of religious pluralism with restrictions through the formal recognition of six official religions to manage diversity within the framework of social harmony. Meanwhile, Turkey is undergoing a transformation from rigid secularism to controlled religious governance dominated by an interpretation of orthodox Islam under the leadership of the AKP. Both countries maintain state control over religious affairs through massive religious bureaucracies such as the MORA in Indonesia and the Diyanet in Turkey. This study confirms that the politics of religious recognition is not just an administrative matter, but a complex political strategy for managing plurality, legitimacy of power, and social stability in multicultural societies. Keyword: Politics of Religious Recognition, Religious Governance, Secularism, Religious Pluralism, Indonesia, Turkey